Electro-Chemo-Mechanics of Solids - Bishop, Sean R.; Perry, Nicola H.; Marrocchelli, Dario; Sheldon, Brian W. (Electronic Materials: Science & Technology,, 2017)
This book brings together a collection of chapters that focus on the relationship among electrical, chemical, and mechanical properties and the study of adjusting one property through the control of another, namely, Electro-Chemo-Mechanics (ECM). The authors examine how this relationship can result in beneficial properties, such as mixed ionic and electronic conductivity, in oxides, upon oxygen deficiency or lithium insertion (electro-chemo) and/or changes in ionic and electronic mobility observed in strained systems (electro-mechano). They also consider how ECM interactions can be responsible for large stresses from non-stoichiometry induced lattice dilation (chemo-mechano). While many volumes are available devoted to the study of the origins and characteristics of electro-chemical relationships, they form the well-known field of electrochemistry, this volume is highly novel in its examination of the corresponding electro-mechanical, chemo-mechanical, and electro-chemo-mechanical relationships. The book is ideal for researchers and design engineers interested in energy storage and conversion and the electrical and mechanical properties of materials.